PERSEPSI MASYARAKAT TERHADAP RUMAH WALET DI KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - Bagas Priyono; Idiannor Mahyudin; Mahfudz Shiddieq; Susilawati Susilawati (EnviroScienteae, 2013)
The purposes of this study were: 1). to analyze public perception of the existence of swiftlet house in their environment; 2). to analyze to analyze relationship characteristics with public perceptions to the presence of swiftlet house. This study was conducted in Palangka Raya City ie RW XII Langkai Village and RW XIII Pahandut Village, Pahandut District, from March to June 2012.   The study was conducted using survey research methods. Determination of the sample is done by purposive sampling method and the data collected are the primary data and secondary data. The analysis based on the average score, sign test, chi square test and rank Spearman correlation test, which presented descriptively. The results showed that the public perception of swiftlet house in study site is not the same. The analysis of data obtained were 30 head of household who refused (60 %) which more than families that received 5 head of household (10% ) and families that hesitant 15 head of household (30 %).  There is a real relationship between public perception of the swiftlet house with residence status shown by X2hitung = 6,480  >  X2tabel= 5,991  residence and distance from the swiftlet house indicated by thitung = 4,35 >  ttabel = 2,01